Phytochemical composition and antioxidant property of Dissotis rotundifolia used for malaria management in south Benin - LAGNIKA, LATIFOU (My University, 2020)
Oxidative stress contributes to induction and progression of many diseases such as malaria. The antioxidant activity of ethanolic and aqueous extracts of Dissotis rotundifolia were investigated using superoxide anion assay, hydrogen peroxide assay, Ferric Reducing Power method and 2, 2-diphenyl-1-picrylhydrazyl assay. Phytochemicals such as total phenolics and flavonoids were assessed by Folin-Ciocalteu and aluminum chloride methods. Ethanolic extract of D. rotundifolia showed the highest phenolic (217.12 ±3.63mg Gallic Acid Equivalent/g) and flavonoid (22.68 ±2.14 mg Equivalent Quercetin/g) contents. The same extract showed a higher antioxidant activity with an IC50 value of 9.93 ±1.62 μg/mL for 2, 2-diphenyl-1-picrylhydrazyl assay. Superoxide anion radical scavenging (59.69 ±2.07%), hydrogen peroxide scavenging (81.73 ±1.29%) and ferric reducing power (910.33 ± 12.52 μmol Ascorbic Acid Equivalent/g) of ethanolic extract were also higher than aqueous extract. Dissotis rotundifolia has potent antioxidant activity which probably contributes to its effectiveness in malaria therapy.
Keywords: Malaria; antioxidant activity; dissotis rotundifolia